2022
DOI: 10.3390/app12010486
|View full text |Cite
|
Sign up to set email alerts
|

Towards Adaptive Gamification: A Method Using Dynamic Player Profile and a Case Study

Abstract: The design of gamified experiences following the one-fits-all approach uses the same game elements for all users participating in the experience. The alternative is adaptive gamification, which considers that users have different playing motivations. Some adaptive approaches use a (static) player profile gathered at the beginning of the experience; thus, the user experience fits this player profile uncovered through the use of a player type questionnaire. This paper presents a dynamic adaptive method which tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Iterative monitoring and adjustments 18. Rodríguez et al ( 2022 ) A dynamic adaptive gamification method which takes players’ profiles as initial information and also considers how these profiles change over time based on users’ interactions and opinions Gamification approaches for e-learning systems in higher education 1. Urh et al ( 2015 ) A model for introduction of gamification into e-learning environments in higher education that consists of the following main elements: management of e-learning, important factors in e-learning, elements of user experience, phases of development (analysis, planning, development, implementation, and evaluation), game mechanics, game dynamics, gamification elements in e-learning and their effects on students.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Iterative monitoring and adjustments 18. Rodríguez et al ( 2022 ) A dynamic adaptive gamification method which takes players’ profiles as initial information and also considers how these profiles change over time based on users’ interactions and opinions Gamification approaches for e-learning systems in higher education 1. Urh et al ( 2015 ) A model for introduction of gamification into e-learning environments in higher education that consists of the following main elements: management of e-learning, important factors in e-learning, elements of user experience, phases of development (analysis, planning, development, implementation, and evaluation), game mechanics, game dynamics, gamification elements in e-learning and their effects on students.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Previous research findings indicate that the successful implementation of gamification in educational contexts requires an adaptive (and not one-fits-all) approach (Rodríguez et al, 2022), wherein the gamified environments are adapted to the user's traits, such as personality type (Buckley & Doyle, 2017), gender (Denden et al, 2021), learning styles (Buckley & Doyle, 2017) and age (Palmquist & Jedel, 2021). The in-depth review of the selected articles also revealed that some scholars related their findings to individual factors, such as gender, prior knowledge and learning style, arguing that their results could be different for learners with different characteristics.…”
Section: Individual Factorsmentioning
confidence: 99%
“…In part, the above gap can be explained by the age difference between professors and their students [71]. Those who design game-based didactic situations naturally tend to strengthen the presence of the player profile that is most in line with their own, so professors should reflect on their own player profile and strive to design gamified situations suitable for player profiles F I G U R E 2 Bartle's classification of player profiles different from their own [22,57,58,69,75,84]. In this article, a first exploration of the player profile of the engineering professors is carried out, from the perspective that they themselves have in this regard, to lay the groundwork for establishing the main differences with the player profiles of the students, more abundantly studied in the literature.…”
Section: Player Profiles Of Engineering Students and Engineering Prof...mentioning
confidence: 99%